(untitled) (Revista Direito em Debate, 2023)
In this article, the administrative, economic, legal and social aspects that inhibited the mortgage crisis related to real estate financing in Brazil were discussed, especially the possible need for State intervention in the economic market. The research was justified in view of the possibility of the occurrence of the aforementioned event on parental soil, following the collapse of the United States in 2008, which caused devastating consequences for that economy. In this perspective, the investigation was important and presented the reasons and difficulties of the recovery of the capital loaned on the mortgage and of a current and widespread use of the fiduciary alienation contract offered by the Brazilian financial institutions as an alternative for the acquisition of real estate and that contributed to the not occurrence of a real estate crisis in Brazilian lands. Lastly, the study used the deductive method, with bibliographical research mainly in legal and economic works, within an analysis that took as a matrix what occurred in the United States of North America in comparison to the Brazilian system, regarding the comparison between the two processes of real estate financing.